Improved back propagation neural network for the diagnosis of pathological voices - Paulraj, M.P.; Sazali, Yaacob, Prof. Dr.; Sivanandam, S. N.; Hariharan, Muthusamy (Association for Advancedment of Modelling and Simulation Techniques in Entreprises (A.M.S.E), 2011)
Link to publisher's homepage at http://www.amse-modeling.com